We have sin (a+b) = (sin a * cos b + cos a * sin b) and cos(a + b) = (cos a * cos b – sin a * sin b)

Also tan (a + b) = [sin (a+b)] / [cos (a+b)]

=> [sin a * cos b + cos a * sin b] / [cos a * cos b – sin a * sin b]

divide all the terms by cos a * cos b

=> [(sin a * cos b)/( cos a * cos b )+ (cos a * sin b)/ ( cos a * cos b )] / [(cos a * cos b)/ ( cos a * cos b ) – (sin a * sin b)/ ( cos a * cos b )]

cancel the common terms in the numerator and denominator and use sin x / cos x = tan x

=> (tan a + tan b)/(1 – tan a * tan b)

Therefore we get:

**tan (a +b) = (tan a + tan b)/(1 – tan a * tan b)**

## We’ll help your grades soar

- 30,000+ book summaries
- 20% study tools discount
- Ad-free content
- PDF downloads
- 300,000+ answers
- 5-star customer support

Already a member? Log in here.

Are you a teacher? Sign up now